Determination of surface runoff using rational method at Al-Sultan Abdullah Hospital, Universiti Teknologi MARA, Puncak Alam / Faridatul Akma Abdul Latif ... [et al.] - Abdul Latif, Faridatul Akma; Khairil Anwar, Danial Iqmal; Mat Isa, Masbiha; Mohamed Ali, Salina; Che Zahari, Mohd Ruzaini (UiTM Press, 2024)
The Al-Sultan Abdullah Hospital development area dominates the ground surface with an impervious surface and few remaining green spaces. This could increase the surface runoff in the area. This study adopted a rational method to determine the amount of surface runoff discharge accumulating on the impervious surface in Al-Sultan Abdullah Hospital. This method considers the catchment area, rainfall intensity, and runoff coefficients. The parameter of rainfall intensity (I) uses the Mononobe formula. In contrast, the weightage average for the total rainfall coefficient (C) and the size of the catchment area (A) is derived from mapping land cover. The results reveal that the total runoff coefficient value is 0.74, meaning that seventy-four percent (74%) of the rainfall becomes surface runoff. The highest surface runoff discharge was on the third of December 2022, with 0.684 m³/s with a rainfall intensity of 17.73 mm/hr. In contrast, the lowest was on the ninth of November 2022 at 0.331 m³/s, with a rainfall intensity of 8.59 mm/hr. The results found that the type and size of land cover influence the runoff coefficient in the study area. The results of this study demonstrate that surface runoff discharge from the site study increased as the impervious surface area increased.